PENGARUH KREDIT SEKTORAL TERHADAP PERTUMBUHAN EKONOMI PROVINSI KALIMANTAN SELATAN - NORHIDAYAH NORHIDAYAH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The purpose of this research is to know the effect of credit distribution of agricultural sector, mining, construction and processing industry to economic growth of South Kalimantan.               The method of analysis performed is multiple linear regression of panel data. This study uses observations of 5 years from 2012 to 2016, the available data is processed using the computer program aids E-views 9.0               Based on the results of the research, in the outcome, agricultural credit disbursement has a negative and significant effect on the economic growth of South Kalimantan. The lending of the mining sector has a negative and insignificant effect on the economic growth of South Kalimantan. The lending of the construction sector has a positive and significant impact on the economic growth of South Kalimantan. The credit distribution of the manufacturing sector has a negative and significant effect on the economic growth of South Kalimantan.Keywords: Distribution of Agricultural Sector Credit, Distribution of Credit in Mining Sector, Distribution of Credit in Construction Sector, Distribution of Credit in Manufacturing and Economic Growth Sectors.